2020
DOI: 10.1084/jem.20192319
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous STAT2 gain-of-function mutation by loss of USP18 activity in a patient with type I interferonopathy

Abstract: Type I interferonopathies are monogenic disorders characterized by enhanced type I interferon (IFN-I) cytokine activity. Inherited USP18 and ISG15 deficiencies underlie type I interferonopathies by preventing the regulation of late responses to IFN-I. Specifically, USP18, being stabilized by ISG15, sterically hinders JAK1 from binding to the IFNAR2 subunit of the IFN-I receptor. We report an infant who died of autoinflammation due to a homozygous missense mutation (R148Q) in STAT2. The variant is a gain of fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 29 publications
0
60
0
5
Order By: Relevance
“…They have also already highlighted the heterogenous phenotypes that can result from variants in the same gene (e.g., CDC42 [ 33 39 , 52 ]), indicated that significant diseases can arise from mono-allelic or bi-allelic loss of function ( IL6ST [ 9 ], RIPK1 [ 42 , 43 ]) or bi-allelic loss- or gain-of-function ( CEBPE [ 24 ], STAT2 [ 40 , 41 ]) variants in the same gene, or from autoAb phenocopies of monogenic lesions (e.g., COVID19 and anti-IFN Abs) [ 48 ], and identified novel somatic mutations as pathogenic causes of immune disorders ( UBA1 ) [ 47 ]. Importantly, they have also provided opportunities for therapeutic interventions, such as JAK inhibitors to treat STAT2 gain of function [ 40 , 41 ] or SOCS1 deficiency [ 22 ], IFNγ to treat mycobacterial disease [ 25 , 26 ], or early IFN-β or IFN-α2a treatment of SARS-CoV2 infection in COVID-19 patients with autoantibodies against IFN-α or IFN-ω [ 67 ] or impaired type 1 IFN responses [ 70 ]. This snapshot of genetic discoveries underpinning human immune disorders further highlights the critical contributions of inborn errors of immunity to our broader understanding of basic, translational, and clinical immunology.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They have also already highlighted the heterogenous phenotypes that can result from variants in the same gene (e.g., CDC42 [ 33 39 , 52 ]), indicated that significant diseases can arise from mono-allelic or bi-allelic loss of function ( IL6ST [ 9 ], RIPK1 [ 42 , 43 ]) or bi-allelic loss- or gain-of-function ( CEBPE [ 24 ], STAT2 [ 40 , 41 ]) variants in the same gene, or from autoAb phenocopies of monogenic lesions (e.g., COVID19 and anti-IFN Abs) [ 48 ], and identified novel somatic mutations as pathogenic causes of immune disorders ( UBA1 ) [ 47 ]. Importantly, they have also provided opportunities for therapeutic interventions, such as JAK inhibitors to treat STAT2 gain of function [ 40 , 41 ] or SOCS1 deficiency [ 22 ], IFNγ to treat mycobacterial disease [ 25 , 26 ], or early IFN-β or IFN-α2a treatment of SARS-CoV2 infection in COVID-19 patients with autoantibodies against IFN-α or IFN-ω [ 67 ] or impaired type 1 IFN responses [ 70 ]. This snapshot of genetic discoveries underpinning human immune disorders further highlights the critical contributions of inborn errors of immunity to our broader understanding of basic, translational, and clinical immunology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently-reported gene defects have been found for most categories of inborn errors of immunity, including novel causes of: SCID ( PAX1 [ 5 , 6 ], SLP76 [ 7 ]); CID ( MCM10 [ 8 ], IL6ST [ 9 11 ]); Predominantly antibody deficiencies ( FNIP1 [ 14 , 15 ], PIK3CG [ 16 , 17 ], CTNNBL1 [ 18 ], TNFSF13 [ 19 ]); Autoinflammatory diseases ( SOCS1 [ 20 22 ], TET2 [ 23 ], CEBPE [ 24 ], CDC42 [ 33 39 ], LSM11 , RNU7–1 [ 32 ], STAT2 [ 40 , 41 ], RIPK1 [ 42 , 43 ], NCKAP1L [ 44 46 ]), UBA1 (somatic mutations) [ 47 ]; and Susceptibility to infection with specific pathogens ( MAPK8 [ 31 ]; TBX21 [ 25 ], IFNG [ 26 ], NOS2 [ 28 ], SNORA31 [ 29 ], ATG4A , MAP1LC3B2 [ 30 ]) (Table 1 ). …”
Section: Novel Causes Of Inborn Errors Of Immunitymentioning
confidence: 99%
See 3 more Smart Citations